Pharmaceutical prospects of Silymarin for the treatment of neurological patients: an updated insight - Ranjan, Shovit; Gautam, Akash (Frontiers in Neuroscience, 2023)
Background Silymarin is a polyphenolic flavonoid complex extricated from dried fruits and seeds of the plant Silybum marianum L. Chemically, it is a mixture of flavonolignan complexes consisting of silybin, isosilybin, silychristin, silydianin, a minor quantity of taxifolin, and other polyphenolic compounds, which possess different bio medicinal values. Purpose This review critically looks into the current status, pharmaceutical prospects and limitations of the clinical application of Silymarin for treating neurological disorders. In particular, Silymarin’s medicinal properties and molecular mechanisms are focused on providing a better-compiled understanding helpful in its neuro-pharmacological or therapeutic aspects. Methods This review was compiled by the literature search done using three databases, i.e., PubMed (Medline), EMBASE and Science Direct, up to January 2023, using the keywords-Silymarin, neurological disorders, cognitive disorders, Type 2 Diabetes, pharmaceutical prospects and treatment. Then, potentially relevant publications and studies (matching the eligible criteria) were retrieved and selected to explain in this review using PRISMA 2020 (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) study flow chart. Result Since its discovery, it has been widely studied as a hepatoprotective drug for various liver disorders. However, in the last 10–15 years, several research studies have shown its putative neuroprotective nature against various brain disorders, including psychiatric, neurodegenerative, cognitive, metabolic and other neurological disorders. The main underlying neuroprotective mechanisms in preventing and curing such disorders are the antioxidant, anti-inflammatory, anti-apoptotic, pro-neurotrophic and pro-estrogenic nature of the bioactive molecules. Conclusion This review provides a lucid summary of the well-studied neuroprotective effects of Silymarin, its underlying molecular mechanisms and current limitations for its usage during neurological disorders. Finally, we have suggested a future course of action for developing it as a novel herbal drug for the treatment of brain diseases.